Selection signature analysis reveals genes associated with tail phenotype in sheep - Qi, Yunxia; He, Xiaolong; Wang, Biao; Yang, Chaoyun; Da, Lai; Liu, Bin; Zhang, Wenguang; Fu, Shaoyin; Liu, Yongbin (Frontiers in Genetics, 2024)
Tail type of sheep, which may be affected by many genes with a complex mechanism, is an important economic trait concerned by both raiser and consumers. Here, we employed two sheep breeds with extreme phenotypes - Mongolian sheep (short-fat-tailed) and Bamei Mutton sheep (long-thin-tailed) to analyze the genetic differences at the genomic level and find candidate genes associated with tail phenotype. The results of population structure analysis showed that the LD decay rate of Mongolian sheep was greater than that of Bamai Mutton sheep. When K = 2, the two populations were obviously separated with a certain degree of mixing. From 49 sheep individuals, 20,270,930 and 2,479,474 SNPs and Indels were identified, respectively. Selection signals were detected based on FST, π-Ratio, and XP-EHH. These three methods identified 85 candidate genes, of which PDGFD, GLIS1, AR, and FGF9 were reported to be associated with tail fat deposition, while VRTN associated with tail length in sheep tail phenotype; the others were novel genes that may play important roles in sheep tail phenotype formation. Gene annotation revealed that these candidate genes mainly participate in pathways associated with fat deposition or lipid metabolism. This study provided insight into sheep tail type development and a guide for molecular breeding.